(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article analyzes, in terms of poetics, situational states of characters in two tales by O. Kuprin and M. Starytsky. The author noted that the situational mental states of these characters are depicted as being very stable. Descriptions of the vitality senso-ry awareness and those situational mental states of the characters, which are generated with these situations, are presented differently in various examples of national litera-ture. Moreover, these are defined by variations in the scenes and plot; specifically the different causes, conditions, motivations, and actions of the characters. However, the essence of both types of situations and situational conditions remain very similar.